Modeling tax revenue determinants: The case of Visegrad Group countries - Jadranka urović Todorović; Marina orević; Vera Mirović; Branimir Kalaš; Nataša Pavlović (Economies, 2024)
This article provides panel data estimations of the tax revenue determinants in VG (Visegrad Group) countries (the Czech Republic, Hungary, Poland, and Slovakia) for the period 1994-2023. The aim of this research was to determine how the macroeconomic determinants affect the tax revenues in the selected countries. Within the static models, the Hausman test showed that the FE (fixed effects) model is appropriate and reflects the significant effects of the gross domestic product, population, inflation, unemployment, import, government revenue, government expenditure, and EU enlargement on the tax revenue. The PMG (Pooled Mean Group) model is an adequate model among the dynamic models and manifests the significant effect of the lagged value of the tax revenue. In the short term, growth of the gross domestic product and population by 1% causes higher changes in the tax revenue of 0.14% and 2.93%. Likewise, growth of the inflation rate by 1% decreases the tax revenue by 0.037%, which is higher than in the long term. Further, the results show that EU enlargement is significant for tax revenue in the short term, as well as in the long term. In the long term, unemployment has a greater significant effect on tax revenue, where 1% growth decreases the tax revenue by 0.15%. In contrast, government revenue is significant for tax revenue only in the long term, where 1% growth increases the tax revenue by 0.77%.
Keywords: 330; determinants; panel regression models; performance; tax revenue; VG countries